Analisis Hubungan Gula Darah Puasa dengan Tekanan Darah pada Pasien Hipertensi dengan Komorbid Diabetes Mellitus - Nurmaya Azzahra; Andi Kartini Eka Yanti; Hidajah Hidajah (Pusat riset dan Inovasi Nasional, 2026)
Hypertension and diabetes mellitus are two highly prevalent non-communicable diseases that often coexist as comorbidities, significantly increasing the risk of cardiovascular complications. The coexistence of these conditions accelerates the onset of atherosclerosis, diabetic nephropathy, and kidney failure, thereby requiring more comprehensive clinical management. One of the key parameters in diabetes management is fasting blood glucose (FBG), which reflects the balance of glucose metabolism after a fasting period. Chronic hyperglycemia is known to contribute to endothelial dysfunction, increased peripheral vascular resistance, and activation of the sympathetic nervous system and renin-angiotensin-aldosterone system, ultimately leading to elevated blood pressure. This study employed a systematic literature review approach, analyzing articles published between 2021 and 2025. Narrative synthesis was conducted across various study designs, including cross-sectional, cohort, and meta-analysis studies. The findings indicate that most studies support a significant association between FBG levels and blood pressure, although some reported varying results. Cohort studies provide stronger evidence that elevated FBG increases the risk of new-onset hypertension. Age, treatment adherence, and lifestyle factors were also identified as confounding variables influencing outcomes. Overall, the evidence highlights that glycemic control through FBG monitoring is essential in managing hypertension among diabetic patients. Multidisciplinary strategies, patient education, and strengthening of primary healthcare services are required to reduce cardiovascular risks. Longitudinal studies are recommended to deepen the understanding of the relationship between FBG and blood pressure and to reinforce the scientific basis for evidence-based clinical interventions.